Il ruolo della ragione e delle emozioni nelle scelte: il caso dei dilemmi morali - Fruciano, Gessica; Raso, Michele (Rivista Italiana di Filosofia del Linguaggio, 2020)
Those who deal with ethics today cannot fail to take into account the theoretical developments that have recently taken place in the field scientific, by biologists, psychologists, social scientists and neuroscientists. It therefore becomes of significant importance to investigate the characteristics of ethical decisions, their being different from other types of decision as well as the role that rationality and emotions play in contexts where the decision between two alternatives is the source of moral conflict. In recent years, an important contribution to research has been provided by the neurosciences that have occurred posed the problem of identifying the neural mechanisms that underlie moral decision and judgment. There is a very particular branch of analytical ethics called «carrellologia» (trolleylogy), which deals with the so-called «problems of the railway carriage», mental experiments structured to analyze the ability to make decisions in extreme but imaginary conditions. They consist in the evaluation of situations in which the ability to make moral intuitions is tested before a choice of life or death. In a recent experiment, Greene and colleagues (2001) presented a series of moral dilemmas to some subjects undergo magnetic resonance imaging (fmri). The most used dilemmas are the trolley dilemma and the footbridge dilemma. What answers have been obtained since the presentation of these experiments? How many cognitive processes, emotions and reason do they influence choice / decision situations?